Associations of composite dietary antioxidant index with suicidal ideation incidence and mortality among the U.S. population - Huang, Shaoqun; Zhao, Weimin; Choi, Seok; Gong, Hongyang (Frontiers in Nutrition, 2024)
The relationship between CDAI and suicidal ideation is unclear. This study investigates the relationship between CDAI and suicidal ideation and examines the association between CDAI and all-cause mortality (ACM) or cardiovascular disease mortality (CVM) among participants with and without suicidal ideation.Methods: Data from seven NHANES cycles (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) were analyzed using crosssectional and prospective cohort studies. Weighted multivariable logistic regression models, restricted cubic spline (RCS) plots, and subgroup analyses explored the association between CDAI and suicidal ideation. Kaplan-Meier (KM) curves, weighted multivariable Cox proportional hazards models, and RCS assessed the relationship between CDAI and CVM or ACM.Results: Among 30,976 participants aged over 20, 1,154 (3.72%) had suicidal ideation.Higher CDAI levels (Quartile 4) were associated with a 28% reduction in suicidal ideation compared to lower levels (Quartile 1). Over an average follow-up of 89 months, 3,267 participants (7.6%) died, including 808 (1.8%) from cardiovascular causes. Higher CDAI levels were linked to a 30%, 68%, and 28% reduction in ACM in the total population, those with suicidal ideation, and those without, respectively. CVM was reduced by 40% in the total population and by 41% in those without suicidal ideation.Conclusions: CDAI is negatively associated with suicidal ideation and correlated with reduced ACM and CVM among participants with and without suicidal ideation.